2019
DOI: 10.1002/1873-3468.13647
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐375‐mediated suppression of engineered coxsackievirus B3 in pancreatic cells

Abstract: Coxsackievirus B3 (CVB3) has potential as a new oncolytic agent for the treatment of cancer but can induce severe pancreatitis. Here, we inserted target sequences of the microRNA miR‐375 (miR‐375TS) into the 5′ terminus of the polyprotein encoding sequence or into the 3′UTR of the CVB3 strain rCVB3.1 to prevent viral replication in the pancreas. In pancreatic EndoC‐βH1 cells expressing miR‐375 endogenously, replication of the 5′‐miR‐375TS virus and that of the 3′‐miR‐375TS virus was reduced by 4 × 103‐fold and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Nevertheless, several studies recently demonstrated that miR-TS can also be inserted into the 3′-UTR of CVB3 without affecting virus propagation. This was achieved by placing the miR-TS immediately downstream of the stop codon of the CVB3 polyprotein [74,103,[107][108][109]. This approach apparently prevents the destruction of critical secondary structures within the 3′-UTR of the virus.…”
Section: Improvement Of the Safety Of Oncolytic Cvb3 By Microrna-mediated Regulation Of Virus Replicationmentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, several studies recently demonstrated that miR-TS can also be inserted into the 3′-UTR of CVB3 without affecting virus propagation. This was achieved by placing the miR-TS immediately downstream of the stop codon of the CVB3 polyprotein [74,103,[107][108][109]. This approach apparently prevents the destruction of critical secondary structures within the 3′-UTR of the virus.…”
Section: Improvement Of the Safety Of Oncolytic Cvb3 By Microrna-mediated Regulation Of Virus Replicationmentioning
confidence: 99%
“…This involved the insertion of miR-TS in a forward orientation to target the plus-strand genome or in a reverse orientation to target the minus-strand replication intermediate of CVB3. All CVB3 containing miR-TS in their plus-strand genome were sensitive to the corresponding miRs [74,103,105,[107][108][109]137]. The miR-targeting of the viral minus-strand is particularly attractive, as CVB3 generates only few minus-strand RNA intermediates during genome replication, which function as template for generating lots of plus-strand RNA genomes [141].…”
Section: Improvement Of the Safety Of Oncolytic Cvb3 By Microrna-mediated Regulation Of Virus Replicationmentioning
confidence: 99%
See 3 more Smart Citations